A MULTIMODAL DISCOURSE STUDY OF #BRINGBACKOURGIRLS CAMPAIGN PROTEST VIDEO CLIPS (2014-2015) - AKPATI , Chibuzor Franklin; ODEGHA , Charity Imodu; OGARAKU, Peace Ngozi (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This study identified and analysed the visual elements used as communicative strategies in BrinGBackOurGirls campaign video clips. It also interpreted the underlying ideologies embedded in the visual elements. These were done with a view to showing how messages are passed or communicated in protest discourse through a critical analysis of multimodal resources. The study employed both primary and secondary sources of data. The primary source comprise video clips of #BringBackOurGirls campaign that took place between 2014 and 2015. Five video clips were downloaded from www.YouTube.com. Five visual elements were extracted from each of the video clip. The secondary source included textbooks, journal articles and the Internet. The data were analysed and interpreted using Multimodal Critical Discourse Analysis (MCDA) approach by Machin and Mayr (2012). The results showed that visual elements such as image, dressing and colour were used to elicit sympathy and create both national and global awareness. The study also revealed the preservation of the abducted Chibok girls lives by the protesters through the use of red colour saturation on their clothes. The study, therefore, concluded that analysis of ideologies embedded in visual elements of any form of protest or media discourse is best understood through the application of multimodal critical discourse analysis approach.